Health and long-term care needs of the ageing population in Sri Lanka: The role of research in making evidence-based social policies - Perera, E.L.S.J. (University of Colombo, Sri Lanka., 2019)
Demographic transitions followed by a significant change in the age-sex structure of the population and increase in life expectancy that have been observed in Sri Lanka over the last two decades are directly related to the country's current and future ageing population.
Keywords: ageing population, elderly health care, elderly health issues, long-term care